Sexual harassment and implicit gender-career biases negatively impact women's life expectancy in the US: a state-level analysis, 2011-2019 - George B. Cunningham; Pamela Wicker (BMC, 2024)
Abstract Background Despite some gains, women continue to have less access to work and poorer experiences in the workplace, relative to men. The purpose of this study was to examine the relationships among women's life expectancy and two work-related factors, sexual harassment and gender-career biases. Method We examined the associations at the state level of analysis (and District of Columbia) in the US from 2011 to 2019 (n = 459) using archival data from various sources. Measures of the ratio of population to primary health providers, year, the percent of adults who are uninsured, the percent of residents aged 65 or older, and percent of residents who are Non-Hispanic White all served as controls. Results Results of linear regression models showed that, after accounting for the controls, sexual harassment and gender-career biases among people in the state held significant, negative associations with women's life expectancy. Conclusion The study contributes to the small but growing literature showing that negative workplace experiences and bias against women in the workplace negatively impact women's health.